2001
DOI: 10.1182/blood.v97.5.1378
|View full text |Cite
|
Sign up to set email alerts
|

Activation of caspase-8 in drug-induced apoptosis of B-lymphoid cells is independent of CD95/Fas receptor-ligand interaction and occurs downstream of caspase-3

Abstract: The activation of caspase-8, a crucial upstream mediator of death receptor signaling, was investigated in epirubicinand Taxol IntroductionApoptosis, a morphologically and biochemically defined form of cell death, 1 plays a role in a wide variety of biologic systems, including tissue homeostasis and regulation of the immune system. 2,3 The process is a highly orchestrated cellular pathway leading to activation of the downstream death machinery. The central mediator and executioner of the death machinery is a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
201
1
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 231 publications
(224 citation statements)
references
References 48 publications
18
201
1
4
Order By: Relevance
“…Recent reports have shown that both caspase-8 and -9 can be activated downstream of each other in both drug-induced and death receptor-induced apoptosis. 45,[61][62][63][64] In apoptosis induced by death receptors, caspase-8 becomes active at the DISC. 44 The active caspase-8 can directly activate downstream caspases such as caspase-3 and -7.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that both caspase-8 and -9 can be activated downstream of each other in both drug-induced and death receptor-induced apoptosis. 45,[61][62][63][64] In apoptosis induced by death receptors, caspase-8 becomes active at the DISC. 44 The active caspase-8 can directly activate downstream caspases such as caspase-3 and -7.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of caspase-3 in the apoptotic response to RanBP1 downregulation is interesting in light of the notion that taxol, which suppresses MT dynamics and causes prometaphase arrest, also induces caspase-3 activation and eventually apoptosis (Ibrado et al, 1998;Oyaizu et al, 1999;Wieder et al, 2001;Lu et al, 2005;Impens et al, 2008). We therefore decided to investigate the combined effect of RanBP1 interference and taxol exposure.…”
Section: Downregulation Of Ranbp1 Levels Render U2os Cells More Sensimentioning
confidence: 99%
“…Activation of caspase-8 was blocked by preincubation of the B lymphoid cells with the caspase-3 specific inhibitor zDEVD-fmk. 93 Thus, in drug-induced apoptosis in B lymphoid cells the molecular order is represented by the hierarchical activation of mitochondria, caspase-3 and downstream caspase-8. In this system caspase-8 functions as an amplifying executioner rather than as an initiator caspase (Figure 2).…”
Section: Initiator and Effector Caspases And Their Targetsmentioning
confidence: 99%
“…93,[149][150][151] This also holds true for the activation of caspase-8 during drug-induced apoptosis. 152 In contrast to the death-receptor/FADD-dependent pathway, caspase-8 activation is triggered in this situation by a receptor-independent, post-mitochondrial mechanism downstream of caspase-3 and functions as an amplifying executioner caspase during drug-induced apoptosis.…”
Section: Death Receptors In Radio-and Chemotherapymentioning
confidence: 99%